A study on drivers perception towards speed limit enforcement in Kota Kinabalu / Azlan Arrifin Saladi and Noorsyazwani Osman - Saladi, Azlan Arrifin; Osman, Noorsyazwani (2014)
Exceeding the speed limit and driving too fast might cause road accidents and severe injuries to the victims. Speeding offense can be considered as one of the factors that might cause traffic crashes and even deaths. Drivers play an important role in this matter because of their attitude towards the speeding may influence their perception towards the speed limit enforcement. Perception of the drivers towards the speed limit enforcement, which being influenced by the attitude of the drivers who did not care about the impacts of speeding might cause loss of lives anytime and everywhere. The purpose of this study was to examine the perceptions of drivers towards the speed limit enforcement in Kota Kinabalu area, the relationship between driver's experiences towards speed limit enforcement and perceptions towards speed limit enforcement and the relationship between drivers' attitude towards speed limit enforcement and perceptions towards speed limit enforcement. This study was done using a self developed questionnaire involving 138 drivers within Kota Kinabalu. From the finding, we can conclude that there was no relationship between the drivers' experience and the perceptions of drivers towards speed limit enforcement. There was a significant relationship between driver attitude towards speed limit enforcement and drivers' perceptions towards speed limit enforcement. It means that the driver's attitude towards speed limit enforcement may influence their perception towards speed limit enforcement.